2020
DOI: 10.1101/2020.05.27.20114017
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling the SARS-CoV-2 first epidemic wave in Greece: social contact patterns for impact assessment and an exit strategy from social distancing measures

Abstract: In Greece, a nationwide lockdown to mitigate the transmission of SARS-CoV-2 was imposed on March 23, 2020. As by the end of April the first epidemic wave is waning, it is important to assess the infection attack rate and quantify the impact of physical distancing. We implemented a survey to assess social mixing patterns before the epidemic and during lockdown. We estimated R0 from surveillance data and assessed its decline as a result of physical distancing based on social contacts data. We applied a Suscepti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 51 publications
(71 reference statements)
1
17
1
Order By: Relevance
“…However, it does imply that this is a possibility and focused research is needed to clarify it. It is in relative contrast with a report suggesting that the lockdown was the strongest measure with 81% or R 0 reduction attributed to it, but the methodology of that study was quite different from ours and based on self-report data ( 6 ). That study also suggested that that only multiple measures implemented simultaneously could reduce R 0 below 1.…”
Section: Discussioncontrasting
confidence: 99%
“…However, it does imply that this is a possibility and focused research is needed to clarify it. It is in relative contrast with a report suggesting that the lockdown was the strongest measure with 81% or R 0 reduction attributed to it, but the methodology of that study was quite different from ours and based on self-report data ( 6 ). That study also suggested that that only multiple measures implemented simultaneously could reduce R 0 below 1.…”
Section: Discussioncontrasting
confidence: 99%
“…As of May 30, there were 2,915 confirmed cases and 175 related deaths in Greece with a death rate of 16 per 1,000,000 population, which is one of the lowest in Europe [ 2 ]. Modelling data suggest that by the end of April 2020, when the first wave of epidemic was completed, the infection attack rate in Greece was 0.12% (95% Crl: 0.06–0.26) which corresponds to 13,200 total infections (95% Crl: 6,206–27,700) and a case ascertainment rate of 19.1% (95% CI 9.1–40.6) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even for a country like Greece, which was one of the countries that took measures very early and succeeded to combat the disease, a relevant study after using a SEIR model was predicting a cumulative number of confirmed cases approximately at 12K with a confidence interval [4.5K,27.5K], see Fig. 3 of [21]. Currently Greece has a cumulative number of 3.4K confirmed cases, smaller even from the lower edge of predicted interval.…”
Section: Failure Of Model Predictionsmentioning
confidence: 99%
“…The model predictions of [21] are presented at their Fig. 1 where the model has been fitted to the available data til April 26.…”
Section: Greecementioning
confidence: 99%
See 1 more Smart Citation